2020
DOI: 10.21856/j-pep.2020.1.04
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: * Работа выполнена в рамках фундаментальной НИР ГУ «Институт охраны здоровья детей и подростков НАМН Украины» «Вивчити механізми впливу гіпоандрогенії на формування соматичної патології в період статевого дозрівання у хлопців (клініко-експериментальне дослідження)» (№ госрегистрации 0117U003008). Учреждением, финансирующим исследование, является НАМН Украины. Авторы гарантируют ответственность за обьективность представленной информации. Авторы гарантируют отсутствие конфликта интересов и собственной финансовой… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…An important role in the period of sexual development, which coincides with the middle school age, is played by thyroid hormones, which are involved in metabolic processes, bone and skeletal formation, growth process, development of sexual characteristics [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important role in the period of sexual development, which coincides with the middle school age, is played by thyroid hormones, which are involved in metabolic processes, bone and skeletal formation, growth process, development of sexual characteristics [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, growth retardation was registered in almost 10% of boys, sexual dysfunction in every sixth adolescent boy, which was twice as common as among girls of the same age group. Previous studies have shown that oxidative stress caused by an imbalance of thyroid hormones in hypothyroidism affects testosterone levels and, consequently, the formation of hypoandrogenism in boys [1,8,16,24]. There is a direct correlation between the content of thyroid hormones and nutritional status, fat content in the body [4].…”
Section: Discussionmentioning
confidence: 99%